Discrete Scaling and Scattering Properties from Atom-Dimer Collision - Tomio, Lauro [UNESP]; Shalchi, M. A. [UNESP] (Springer Nature, 2020)
A recent proposal on a new perspective to detect the Efimov-like discrete scaling in ultra-cold binary mixtures with strong mass-imbalanced atomic species is communicated. The discrete scaling can be identified by the energy dependence of an atom-molecule elastic cross-section, when colliding a heavy atom with mass (formula presented) into a weakly-bound heavy-light ((formula presented)) dimer. In the extreme mass-imbalanced system it was verified that the s-wave elastic cross section presents zeros at several specific energies of the projectile, in which emerges a discrete behavior from the ratio between these energies. This discrete behavior is identified with the same one predicted for the trimer excited bound-states, when considering the same mass-imbalanced system in the unitary limit.